Corporate governance criteria as applied in private equity investments - R. Millson; M. Ward (South African Journal of Business Management, 2005)
Ineffective governance has often formed a backdrop to corporate failure with the resultant negative impact on stakeholders. In the field of private equity, investors have consistently received financial returns that outperform those of listed equities. This research investigates the relationship that private equity principals seek with their agents.The "agent-principal" relationship in private equity investments was investigated through a literature review and a survey of experienced private equity practitioners identified the key characteristics associated with this relationship. A conjoint analytical technique was used to measure the relative importance of the various attributes and the degree of preference or utility value for these attributes amongst a sample of 27 experts.The field research established that private equity investments are characterised by, inter alia, proactive agent-principal relationships; a relatively high level of shareholder activism; insistence on transparency; non-executive influence; and active performance management. While the implementation of these lessons may be a subject for future research, the current research has identified and prioritised corporate governance mechanisms that may be more generally applied.
Keywords: 650